What's a duke got to do with it - Britton, Christina (Romance fiction writer) (Britton, Christina (Romance fiction writer). Synneful spinsters, 2023)
The last thing Katrina Denby expected to find in her garden is the body of the man who ruined her three seasons ago. No matter that his death is a tragic accident, the rumors are enough to kill any woman's prospects. With two scandals now hounding her, the best she can hope for is a hasty marriage of convenience--until her first love shows up in her drawing room, reminding her of all the reasons why she wanted a love match. If only he weren't already engaged. . . Sebastian Thorne, Duke of Ramsleigh, knows what he has to do to save the dukedom from the crushing debts and scandal his father left: marry and marry well. He's picked the lady, too--a baron's daughter who is pleasant, if a little boring. But seeing Katrina again makes him want to throw all those perfectly laid plans out the window. The first chance he had with her, he chose his duty over his heart. Doing so again might prove utterly impossible.